Investigating the integrative approach and presenting strategies for the integrative approach in psychotherapy and counseling - Tabatabaeifar , Seyed Mahdi; Eshghi, Nasrin; Sonqori , Faezeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Background and Aim: Today, integrative approaches in psychotherapy and counseling have attracted the attention of psychologists. In this regard, researchers have done more and more research, and research evidence is also based on the good effects of integrated approaches. Therefore, the current research aims to examine integrative approaches and provide strategies for an integrative approach in psychotherapy and counseling. Methods: The current research is a review and analytical research using the library method to collect data. In this way, relevant articles and books were obtained by searching for the keyword integrative approach in reliable scientific and research databases. Results: The review of sources showed different strategies for formulating an integrative approach, among which we can refer to the six strategies proposed by Maherer (1989), procedural strategy, and framework strategy. Conclusion: Analyzing the research findings, using a dynamic and process strategy in integration and considering the approaches that integrators paid less attention to can be useful